Production of pulverised fuel ash tiles using conventional ceramic production processes - Bou, E.; Quereda, M. F.; Lever, D.; Boccaccini, Aldo R.; Cheeseman, C. R. (Advances in Applied Ceramics, 2009)
The feasibility of manufacturing sintered ceramic tiles containing a high proportion of pulverised fuel ash (PFA) using conventional ceramic tile processing methods has been investigated at pilot plant scale. From earlier laboratory experiments, a composition containing 92.0 wt-%PFA, 5.0 wt-% sodium bentonite and 3.0 wt-% talc produced good quality small disc samples. The scale-up trials reported here used this same composition and involved deflocculant addition, wet milling, spray drying, pressing and firing, with the behaviour during each processing stage being characterised. Although there were no substantial technical problems associated with forming green tiles, the composition selected needed high levels of deflocculant and produced pressed samples with low green densities, resulting in high shrinkage during firing. The high dependence of shrinkage on temperature caused excessive tile distortion. In addition, sintered samples with less than 2% water absorption exhibited a bloating effect, resulting in poor surface quality. Possible solutions to the problems encountered during the pilot scale trials are considered and the potential commercial viability of high PFA content ceramic products is discussed. © 2009 Institute of Materials, Minerals and Mining Published by Maney on behalf of the Institute.
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.produc
Keywords: Ceramics; Fly ash; Pulverised fuel ash; Reuse; Sintering; Waste